Information seeking behavior of university students during 2023 dengue outbreak: A developing country perspective - Raiyan Bin Reza; Rumana Rahman (Record and Library Journal, 2023)
Background of the study: Dengue outbreak has become a regular phenomenon  Bangladesh. It has created a panic among people from all walks of life. Purpose: The study was conducted to gain insights about the dengue related information seeking behavior of university students of Bangladesh during 2023 dengue outbreak. Method: In this study, a survey was conducted with an online questionnaire here. 532 students from different universities of Bangladesh have participated Mann Whitney and Kruskal Wallis test was applied to determine the relationships between different demographic variables and the choice of information sources, purpose of seeking information. Findings: In this study majority of students Majority of the students use social media platforms as their primary source of information regarding dengue virus. Most of the students seek information to mainly know about the disease and the safety products related to the virus. There was a significant difference between the residence of the respondents and their choice of information sources. The respondents also have identified several barriers to dengue related information. They mostly regarded the lack of medical terminologies and lack of necessary steps by the educational institutions as the primary barriers. Conclusion: Dengue outbreak has become regular phenomenon in Bangladesh. It imperative for studen5tts to seek necessary information regarding the dengue virus. The authorities must take care of the preference of the students regarding the choice information source while giving them proper information.